A comparative study on the combustion process and emissions formation of a CI engine fueled with isomers n-octanol and di-n-butylether. (15th January 2023) - Li, Jing; Liang, Yifei; Yang, Wenming; Wu, Shaohua
Highlights: Numerical study was done on the CI engine fueled with two C8 biofuels OCT and DnBE. The soot particle dynamics calculation was considered during simulation. The effects of two C8 fuels on engine combustion and emissions were compared. The engine fueled with DnBE exhibits a longer combustion duration and low CO. The engine fueled with n -octanol generates less NO and soot emissions. Abstract: Two C8 biofuels, n -octanol (OCT) and di- n -butylether (DnBE), have attracted much attention due to their potential to replace diesel. In this work, compression ignition (CI) engines fueled by OCT and DnBE were numerically compared in terms of combustion characteristics and emissions formation. The KIVA4-CHEMKIN code package was used to model the combustion process in the cylinder. To realize detailed chemistry calculation, a multi-component reaction mechanism including OCT and DnBE was implemented in the code. Also, a mono-variate spherical soot model based on the moment projection method was integrated to handle the soot particle dynamics calculation. The engines fueled with OCT and DnBE were operated under the same condition. The comparison results suggest that the DnBE fueled engine exhibits a shorter ignition delay than the OCT fueled engine due to the rapid evaporation process and high cetane number of DnBE. As a result of earlier ignition, the DnBE fueled engine shows a mixing-controlled combustion regime and a longer combustion duration. The DnBE fueled engine generates more NO emissions because of its higher peak in-cylinder temperature and longer combustion duration. In the bowl region of the combustion chamber, a leaner mixture could be observed for the OCT fueled engine. Consequently, the OCT fueled engine produces less particle number and mass, but higher CO emissions.